An inter-laboratory comparison of standard membrane-feeding assays for evaluation of malaria transmission-blocking vaccines. (December 2016) - Miura, Kazutoyo; Stone, Will; Koolen, Karin; Deng, Bingbing; Zhou, Luwen; Gemert, Geert-Jan; Locke, Emily; Morin, Merribeth; Bousema, Teun; Sauerwein, Robert; Long, Carole; Dechering, Koen
Abstract Background An effective malaria transmission-blocking vaccine may play an important role in malaria elimination efforts, and a robust biological assay is essential for its development. The standard membrane-feeding assay (SMFA) forPlasmodium falciparum infection of mosquitoes is considered a "gold standard" assay to measure transmission-blocking activity of test antibodies, and has been utilized widely in both non-clinical and clinical studies. While several studies have discussed the inherent variability of SMFA within a study group, there has been no assessment of inter-laboratory variation. Therefore, there is currently no assurance that SMFA results are comparable between different studies. Methods Mouse anti-Pfs25 monoclonal antibody (mAb, 4B7 mAb), rat anti-Pfs48/45 mAb (85RF45.1 mAb) and a human polyclonal antibody (pAb) collected from a malaria-exposed adult were tested at the same concentrations (6–94 μg/mL for 4B7, 1.2–31.3 μg/mL for 85RF45.1 and 23–630 μg/mL for human pAb) in two laboratories following their own standardized SMFA protocols. The mAbs and pAb, previously shown to have strong inhibition activities in the SMFA, were tested at three or four concentrations in two or three independent assays in each laboratory, and percent inhibition in mean oocyst intensity relative to a control in the same feed was determined in each feeding experiment. Results Both monoclonal and polyclonal antibodies dose-dependently reduced oocyst intensity in all experiments performed at the two test sites. In both laboratories, the inter-assay variability in percent inhibition in oocyst intensity decreased at higher levels of inhibition, regardless of which antibody was tested. At antibody concentrations that led to a >80 % reduction in oocyst numbers, the inter-laboratory variations were in the same range compared with the inter-assay variation observed within a single laboratory, and the differences in best estimates from multiple feeds between the two laboratories were <5 percentage points. Conclusions This study confirms previous reports that the precision of the SMFA increases with increasing percent inhibition. Moreover, the variation between the two laboratories is not greater than the variation observed within a laboratory. The findings of this study provide guidance for comparison of SMFA data from different laboratories.